Impact of Polygamy Practices in Urban Communities in Kramatjati, East Jakarta - Aziz, Abdul (Mazahib, 2025)
This study explores the dynamics of polygamous practices in the urban community of Kramatjati, East Jakarta, by assessing the impact of official permits and unofficial permits on family relationships and household harmony. The background of this issue discusses the influence of polygamy permits on family life in urban contexts, as well as the various challenges and conflicts that arise as a result of the practice. This article answers this question using an in-depth interview method with seven couples who practice polygamy, whether they have an official permit or not. The theories applied include family communication theory and conflict management. Research findings show that although official permits provide legitimacy, the success of polygamy practices in creating family harmony is highly dependent on internal management and the quality of communication between family members. Couples who have official permission but do not manage the relationship well experience significant tension and conflict, while well-managed couples show relatively stable harmony. In conclusion, formal permits are not enough to guarantee the welfare of the family; Effective management and open communication are the keys to achieving prosperity in the practice of polygamy. However, this does not mean that the researcher supports the practice of polygamy, but rather reflects the reality that occurs in the field.